Acidified water extraction increases carpaine yield from Carica papaya L. Leaf - Sim, Tze Tak; Nor Hisam, Zamakshshari; Mohamad Fhaizal, Mohamad Bukhori; Eswaran, Madiahlagan; Rafeah, Wahi; Lawrence, Anchah (Malaysian Society for Molecular Biology and Biotechnology, 2024)
Carica papaya leaves have been traditionally used in various medicinal applications. The major alkaloid, carpaine, is widely studied for its anti-thrombocytopenic activity. However, extraction of carpaine from Carica papaya leaves remains challenging, and the existing methods may not yield high amount of carpaine due to the presence of various interfering compounds. High carpaine yields are essential for studying on its anti-thrombocytopenic and immunomodulatory effects, assessing its efficacy and safety as a potential malaria drug candidate. This study aims to extract and isolate carpaine from Carica papaya leaves using alcohol extraction method and acidified water extraction method performed on dried powdered leaves and compare their percentage yield of carpaine. The percentage yield of carpaine isolated from acidified water extraction was 12.01%, while the yield for alcohol extraction was 2.18%. Acidic condition enhances carpaine's water solubility through protonation, converting carpaine in its free base form to salt form which improves extraction efficiency. Heat and stirring further optimize the acidified water extraction process. Characterization of isolated carpaine was performed with various analytical techniques to confirm the structure of carpaine isolated.